THE INFLUENCE OF ONLINE GAME TOWARDS STUDENTS' VOCABULARIES CAPTURED DURING GAME PLAYING BY SCHOOL AGE YOUTH - Agung Kurniawan; Nurdin Noni; Samtidar Samtidar (JTechLP: Journal of Technology in Language Pedagogy, 2022)
The study was intended to investigate whether or not Online Games can help students capturing vocabularies during the game by school age youth. The research applied quantitative case study design. The researchers using questionnaire and vocabulary test (online game reference), the questionnaire act as a factor to determine the factor of students’ vocabularies captured and to help strengthen the test result. The population of this research was the students who play and form groups to play online games and participate in the local gaming tournaments, with the age ranging from 14-17 years old. The sample of this research was students who played the online games (PUBGM, FF, ML/MOBA) more than 2 months which were chosen by using purposive random sampling and the researchers set criteria for the sample. The result of the study showed that the test mean score is 89,21 (Good/High), questionnaire agreement level from items 1-10 (High-Very High), and subjects item select category mean score is 74% (High) are align. With the questionnaire serves as a tool to determine the factors in online game that influence the students captured vocabularies, the researchers find out that it is due to the intensity of playing, game features, player base influence, and the player habits in online game.